Heme-peroxidase from medicinal plant Artocarpus lakoocha: Purification, characterization and wound healing studies. Issue 2 (April 2015) - Sonkar, Kirti Shila; Pachauri, Manendra; Kumar, Amit; Shukla, Ankita; Patel, Monika; Jagannadham, Medicherla V.
Abstract: Artocarpus lakoocha is a medicinal plant used in cosmetics and traditional remedies of many diseases. We have purified a protein from its latex using anion exchange chromatography and gel filtration, which resulted in 28.82% yield of protein, with specific activity of 10.8 units/mg. FPLC spectroscopy and isoelectrofocusing demonstrated that purified protein has molecular mass of 53 kDa with isoelectric point of pH 7.4. Isolated peroxidase consists of 17 tryptophan, 14 tyrosine, and 8 cysteine residues per molecule with extinction coefficient of 16.3 M −1  cm −1 . The pH and temperature optima for this peroxidase are 6.0 and 55 °C respectively. MALDI-TOF/TOF was done and MASCOT analysis specified that isolated protein is a peroxidase. Isolated peroxidase shows oxidizing activity with various phenolic substrates like guaiacol, o -phenylenediamine, aminoantipyrine and pyrogallol with K cat 1.90, 0.74, 3.22, 1.49 s −1 respectively. Stability experiments with chemical denaturants, metal ions and organic solvents indicate that isolated protein is very stable under studied conditions. Spectroscopic studies, like absorbance, fluorescence, and circular dichroism reveal that the peroxidase has α / β type secondary structure with approximately 42.6% α -helix, 9.7% β -sheet. In vitro scratch wound healing assay and oxidative damage protection experiments via MTT assay demonstrate that purified peroxidase have wound healing properties. In conclusion, this novel peroxidase is stable at various conditions and helps in healing which hints it׳s potential to be used in inflammation prevention, wound healing, and other biotechnological and industrial applications.